EVALUATION OF SUBCLINICAL VESTIBULAR DYSFUNCTION IN TYPE II DIABETES MELLITUS-CORRELATING WITH HBA1C - PRAKASH.M; SUMATHI.K. (International Journal of Pharma and Bio Sciences, 2013)
The vestibular system, both central and peripheral, is likely to be affected by micro angiopathy due to diabetes mellitus. Subclinical vestibular dysfunction is defined as those patients who do not have symptoms but evidence of the same in relevant investigations. The aim of the study is to find the proportion of subclinical vestibular dysfunction in type II diabetes and to correlate with glycated Hb values. A case control study of 100 patients with and 100 without diabetes mellitus, but both without any symptoms of vestibular dysfunction were subjected to electronystagmography. Clausen butterfly chart is generated based on the bithermal caloric stimulation and the code is ascertained. HbA1c was estimated for these patients by Ion-Exchange Chromatography. Among the total of 100 patients with diabetes 42% had vestibular dysfunction, 58% were normal. Among the controls 12% had vestibular dysfunction, 88% were normal. It is also found that 30% of diabetic patients with vestibular dysfunction had more than four years duration of diabetes. Also HbA1c value is raised in 78% of diabetics. It is evident that the proportion of vestibular pathology is higher among diabetes mellitus. This needs to attend too strictly because vestibular dysfunction combined with hyper or hypoglycemia, poor sight (old age & DM), infirmity (due to old age) and osteoporosis leads to a higher incidence of “fall” which has significant morbidity and mortality especially among elderly.